Money Waqf Regulation and Dynamics of Productive Waqf Asset Governance: A Socio-Legal Study on the Qurani Pamekasan Insan Foundation - Samheri; Misbah Zulfa Elizabeth; Ahmad Furqon; Achmad Gunaryo (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Since the MUI fatwa regarding cash waqf was issued on May 11 2002 and the Law on waqf number 41 of 2004 and PP Number 42 of 2006 was issued, nazir is considered a pillar of waqf waqf. Nadzir is considered an important element in waqf management in developing waqf assets significantly. This research discusses how to update cash waqf regulations in the management and development of waqf assets in Indonesia? How is the implementation of cash waqf regulations at the Insan Qur'an Foundation?  What is the impact of the implementation of cash waqf regulations on Insan Qurani Indonesia Pamekasan Madura? This research uses qualitative research methods, with field research. With a normative-sociological approach. The findings from this research show that changes to waqf regulations regarding the management and development of waqf assets in Indonesia, the implementation of cash waqf regulations at the Indonesian Insan Qurani Foundation opened up opportunities and awareness for the Pamekasan community regarding the urgency of empowering productive waqf for the sake of realizing welfare and social justice. Waqf regulations can make it easier for Nazirs to develop productive waqf in Indonesia. Cash waqf has made a positive contribution to the development of Quran houses, trade, agriculture and livestock under the Insan Qur'an Foundation, expanding access to education and creating new jobs. This research offers an in-depth view of the practice of cash waqf as an effective strategy in developing waqf land assets in Indonesia, with the Insan Qur'an Foundation as the locus of this research study.